Respuestas

¡La mejor respuesta!
2013-10-26T02:26:07+02:00
LLevamos a la minima expresion:
1)  3,67x10^2+8,23x10^12 = 0,000000000367x10^12+8,23x10^12                                                                         =8,230000000367x10^12

2)  
5,78x10^(-9)+(-4,78x10^(-18)) = 5,78x10^(-9)-4,78x10^(-18)
                         = 
5,78x10^(-9) - 4,78x10^(-18)x10^9x10^(-9)
                         = [5,78 - 4,78x10^(-18)x10^9]x10^(-9)
                         = [5,78 - 0,00000000478]x10^(-9)
                         = 5.77999999522x10^(-9)

3)  -4,78x10^(-18)+8,78x10^32 = -4,78x10^(-18)x10^(-32)x10^32+8,78x10^32
                         = [
-4,78x10^(-50) + 8,78]x10^32
                      = [-4,78x10^(-50) + 8,78]x10^32

4)  9,35x10^45-8,23x10^12= [9,35x10^33-8,23]x10^12

5)  3,67x10^2+(-4,78x10^(-18)) = 3,67x10^2x10^18x10^(-18) - 4,78x10^(-18)
                                             = [3,67x10^2x10^18 - 4,78]x10^(-18)
                                             = [3,67x10^20 - 4,78]x10^(-18)